Model Corporate Social Responsibility Pt. Astra International, Tbk - Bagus Styoko Purwo; Bayu Pratama (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2017)
The corporation's current business is no longer prioritize profit as a principal objective. In addition to meeting the business targets, the corporation also must meet eligibility standards as an ethical corporation. Corporate ethics demonstrated by the willingness of corporate conduct sound business. With the presence of the concept of social responsibility for corporations to raising awareness of responsible okum. Implementation of social responsibility that has been initiated by many public companies have a variety of formats. With the enactment of the legal basis for the implementation of Corporate Social Responsibility (CSR) No. legislation. 40/2007 on limited liability companies, which implies the core is the obligation for companies that utilize natural resources to implement CSR using the adjusted cost allocation policy of each company. PT. Astra International, Tbk as one of the largest public company that developed in Indonesia, has been implementing CSR as part of its core activities. Through CSR programs that have been organized Astra certainly have a pattern that needs to be studied scientifically to better administration of the reporting form CSR programs. The question is how the pattern of implementation of Corporate Social Responsibility applied PT. Astra International, Tbk., How activity reports that are used for its Corporate Social Responsibility and how achievement of implementation of Corporate Social Responsibility. The purpose is to study the implementation of Corporate Social Responsibility organized by PT. Astra International, Tbk, to analyze activity reports used to Corporate Social Responsibility program, and to an adequate standard of implementation of Corporate Social Responsibility. The research method used is descriptive qualitative method of data collection techniques through descriptive and focused observation. Data analysis techniques with a qualitative descriptive analysis on the implementation of CSR Astra, reporting CSR activities and CSR benefits. The results of this research form the characteristic pattern of CSR Astra in its execution through foundations established Group Astra, a report prepared Astra sustained economic indicators that show a 10% gain, environmental indicators by 32%, labor practice indicators reached 12.8%, Human rights indicators gained 5.1%, the social indicators by 1.2%, and product responsibility indicators by 5.1%. Revelations of global CSR reports Astra 65%. This shows the suitability of the company's standards of an ongoing report terbatasakuntabilitas, transparency, harmonious relationships with stakeholders, and the achievement of sustainable CSR community perceived the Astra. With the research is expected to be an additional reference on CSR.